MUHAMMADIYAH YOUTH DEVELOPMENT EFFORTS TO BE A SKILLED HEALTH CARE TO DO BASIC LIFE SUPPORT - Irfan Hamdani; Debby Mirani Lubis; Meizly Andina (IHSAN : JURNAL PENGABDIAN MASYARAKAT, 2019)
One of the efforts in improving public health is by promoting health promotion in the school environment and forming health cadres that can be utilized within the school environment (UKS) and the community. Basic Life Support is a skill needed to deal with emergency cases that often occur in the community, one example is sudden cardiac arrest. This case requires immediate treatment and delays in handling will result in death. It is unfortunate, our society is still very unfamiliar with this skill so that in many cases it cannot be helped because they only hope for medical assistance to come, even though it should be handled until the arrival of the medical team so that victims can be saved. The method of approach taken is through a participatory approach. The Proposing Team and partners together develop a plan of activities, methods, goals, objectives and targets that must be achieved. This activity began with the development of Muhammadiyah youth as school health cadres. The training activities were carried out in the form of health seminars, Muhammadiyah cadre character seminars and Basic Life Support workshops for Muhammadiyah high school students. Keywords: Basic Life Support, school, muhammadiyah